Maternal health in pregnancy and associations with adverse birth outcomes: Evidence from Growing Up in New Zealand. (26th October 2016) - Bird, Amy L.; Grant, Cameron C.; Bandara, Dinusha K.; Mohal, Jatender; Atatoa‐Carr, Polly E.; Wise, Michelle R.; Inskip, Hazel; Miyahara, Motohide; Morton, Susan M.B.
Abstract : Objective: To examine prospectively multiple indicators of pregnancy health and associations with adverse birth outcomes within a large, diverse sample of contemporary women. Design: A cohort of pregnant women who gave birth during 2009–10. Population: We enrolled a sample of 6822 pregnant New Zealand (NZ) women: 11% of all births in NZ during the recruitment period. Methods: We analysed a number of maternal health indicators and behaviours during pregnancy in relation to birth outcomes using multivariable logistic regression. Associations were described using adjusted odds ratios and 95% confidence intervals. Main outcome measures: Three birth outcomes, low birth weight (LBW), pre‐term birth (PTB) and delivery type, were measured via linkage with maternity hospital perinatal databases. Small for gestational age (SGA) was then defined as below the 10th percentile by week of gestation. Results: Modelling of birth outcomes after adjusting for confounders indicated patterns of increased risk of LBW and PTB for women who smoke, have elevated pre‐pregnancy body mass index (BMI), or with insufficient pregnancy weight gain. SGA was associated with maternal smoking, alcohol use, insufficient weight gain and nausea and vomiting during pregnancy. Risk of caesarean section was associated with having a diagnosed illness before pregnancy, elevated BMI, greater pregnancy weight gain and less pregnancy exercise. Number of risk factor variables were then used to model birth outcomes. Women with multiple risk factors were at increased risk compared with those who had no risk factors. Conclusions: Women with multiple health risks are at particular risk of adverse birth outcomes.